From Guided Surgery to Final Prosthesis with a Fully Digital Procedure: A Prospective Clinical Study on 15 Partially Edentulous Patients - Giorgio Andrea Dolcini; Marco Colombo; Carlo Mangano (International Journal of Dentistry)
Scope. To demonstrate guided implant placement and the application of fixed, implant-supported prosthetic restorations with a fully digital workflow. Methods. Over a 2-year period, all patients with partial edentulism of the posterior maxilla, in need of fixed implant-supported prostheses, were considered for inclusion in this study. The protocol required intraoral scanning and cone beam computed tomography (CBCT), the superimposition of dental-gingival information on bone anatomy, surgical planning, 3D-printed teeth-supported surgical templates, and modelling and milling of polymethylmethacrylate (PMMA) temporaries for immediate loading. After 3 months, final optical impression was taken and milled zirconia frameworks and 3D-printed models were fabricated. The frameworks were veneered with ceramic and delivered to the patients. Results. Fifteen patients were selected for this study. The surgical templates were stable. Thirty implants were placed (BTK Safe®, BTK, Vicenza, Italy) and immediately loaded with PMMA temporaries. After 3 months, the temporaries were replaced by the final restorations in zirconia-ceramic, fabricated with a fully digital process. At 6 months, none of the patients reported any biological or functional problems with the implant-supported prostheses. Conclusions. The present procedure for fully digital planning of implants and short-span fixed implant-supported restorations has been shown to be reliable. Further studies are needed to validate these results.